The Fathers’ Illusion of Redemption, Their Children’s Perception of Pain: Migratory, Family, and Intergenerational Trajectories of Italian-Bangladeshis Relocating to London - Della Puppa, Francesco (Italian Sociological Review, 2025)
This article is the result of a broader research project on the onward migration of Bangladeshi migrants in Italy who, once they have acquired Italian citizenship – and so a European passport – set off on a new migration to London, just before the “Brexit” referendum. The empirical evidence for the article comes from 40 in-depth interviews 1) with Italian-Bangladeshi men who have either already onward-migrated or are planning on doing so, and 2) with some of their children. The main motivation for this onward migration is the investment of first-migrant fathers in their children. Born and socialized in Italy, this so-called “second generation” have formal Italian citizenship, but are still subjected to processes of racialization and experience discrimination in public spaces and in political and media debates, and are also at risk of following their fathers into unskilled factory work, despite having acquired educational qualifications. The strategy for dealing with this “effect of destiny” is a “leap forward” into a context perceived – and idealized – as more meritocratic and governed by multiculturalism in which their presence would not need to be justified. However, the new migration is experienced by their children as a form of uprooting, similar to what their fathers experienced.